BASELINE SURVEY OF TSANGAYA QUR’ANIC SCHOOLS IN TARABA STATE NIGERIA - Tijjani Usman Karofi (Universitas Muhammadiyah Surakarta, 2024)
This paper titled Baseline Survey of Tsangaya Qur’anic Schools in Taraba State is research on the various Tsangaya schools in Taraba State. The survey is a comprehensive mapping exercise on the existing traditional Tsangaya Qur’anic schools in Taraba State to provide concrete and verifiable data on the Tsangaya (traditional Qur’anic schools) in the entire State. The generated data was tabulated and analyzed using simple percentages as the suitable statistical method of computing the findings. The major findings of the survey were analyzed, revealing 900 functional Tsangaya Schools and their respective proprietors. While 3,409 teachers were pencilled in, 61,882 enrollment figures were recorded in the survey. The carrying capacity of the schools across the State stands at 80,749, while the total enrollment as of the period covered by this survey is 61,882, showcasing a glaring gap of 18,867. Community goodwill and support were the most pressing peculiarly needs of Tsangaya Qur’anic schools, while sanitation represented the least on the list. Thereupon, recommendations on needful measures for effective mitigation of the plights of the traditional (Tsangaya) Qur’anic school system in Taraba State were proffered, stressing the perennial need for strategic intervention/investment in Tsangaya Qur’anic schools by all relevant bodies with the view to rewind-the-past-glory-of-the-system.